The Current of Population Aging and Its Impact on Economic Growth in the Mekong Delta - Thuan, Phan; Thu Hien, Vu Thi (VNU Journal of Science: Policy and Management Studies, 2020)
The purpose of the article is to analyze the current of aging population and its impact on economic growth in the Mekong Delta. The article pointed out that aging population has being occured quickly with the trends: the rapid increase of group population aged 60 and over, the differences between localities in the area and the elderly population feminization. This has impacted strongly on the region's economic growth. From the evidences of this study, aging population has influenced both positive and negative to the region's economic growth.